The Strategy of Da'wah Bil Hikmah in the Formation of Student Characters: Ethnographic Study in Class XI of Integrated Islamic High School Darul Hasan - Sayyed Makmur El Rasyidy; Moh. Iqbal Abdul Muin (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2026)
This study examines the strategy of da‘wah bil hikmah in the formation of student character through an ethnographic study conducted in Grade XI at SMA Islam Terpadu Darul Hasan, Padangsidimpuan City. In the context of contemporary educational challenges marked by globalization and rapid technological development, character formation based on Islamic values requires pedagogical strategies that are contextual, humane, and adaptive to students’ psychological and social conditions. Employing a qualitative research design with an ethnographic approach, this study collected data through participant observation, in-depth interviews, and documentation involving the school principal, Islamic Education teachers, and students. The findings reveal that da‘wah bil hikmah is implemented through wise instructional delivery, gentle and persuasive communication, dialogical interactions, and teacher exemplification, which collectively contribute to a psychologically safe and morally supportive learning environment. These practices foster the internalization of Islamic character values, including religious obedience, respect for teachers, discipline, empathy, responsibility, critical attitudes, and tolerance toward differences in religious understanding. However, the study also identifies several challenges, such as variations in students’ motivation and comprehension, limited instructional time, the influence of social media, and inconsistent parental support. Overall, the study concludes that da‘wah bil hikmah, when systematically planned and supported by teachers, school leadership, structured programs, and positive peer environments, serves as an effective and sustainable strategy for holistic character formation in integrated Islamic secondary education.